Critical analysis on the children and young person Employment Act 1966 and the Education Act 1996 in relation to causes and effect of child labor in Malaysia - Nik Mahmod, Nik Ahmad Kamal; Che Mohd Salleh, Marhanum; Mohamed, Azizah; Ali Mohamed, Ashgar Ali; Amuda, Yusuff Jelili (GATR Enterprise, 2015)
Objective – It is observed that the phenomena of working children is a long-standing issue in most under-developed and developing countries of the world and the number increases each year in the light of challenging domestic social and economic conditions. The question is whether the relevant law has a special exemption to allow children to work and to what extent the law accommodates scenarios obtained from the empirical study for the purpose of this research? The objective of this research is to examine the reason children goes to work instead of pursuing an education. Methodology/Technique – The survey involved interviewing through a set questionnaire 557 working children in six states in Malaysia. Based on the survey, the Children and Young Person Employment Act 1966 is critically reviewed to evaluate the scope of protections for working children in Malaysia. Findings – Based on the empirical analysis, it is found that the majority of the working children in Malaysia worked to help their family economically and they are not happy with their current job. The children in this context reported that they regretted not attending school as their have to work to help their family. Novelty – By adopting content analysis on the current act, this research discovers that due to lack of efficient implementation of existing legal regimes, especially the Education Act 1996 to deal with an issue pertaining to children not attending schools. This research concludes that effective implementation of all legislation dealing with working children and their compulsory education may have a positive impact on overall child labor management in Malaysia.